A negatively charged nanofiltration membrane, its preparation method and application
Patent Information
- Application Number
- CN202611315273.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-16
AI Technical Summary
该膜可应用于盐湖处理但膜通量不足
(1)本发明在支撑层上通过两次界面聚合形成了荷负电的聚酰胺分离层,并且接枝了大量磺酸基团而后通过原位诱导聚合的方法引入了刚性的改性层,通过这两层的结合大大增强了膜表面的负电性、亲水性以及稳定性。
Smart Images

Figure CN122912693A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane separation technology, and in particular to a negatively charged nanofiltration membrane, its preparation method, and its application. Background Technology
[0002] Negatively charged nanofiltration membranes are selective separation membranes based on pressure-driven separation technology. Their surfaces possess fixed negatively charged groups, achieving efficient separation of solvents and solutes through a synergistic mechanism of pore size sieving and charge repulsion. The separation mechanism depends not only on the nanoscale pore size of the membrane material but also significantly on the surface charge characteristics. The negatively charged membrane surface can repel anionic solutes through the Donnan effect while preferentially adsorbing cations, thereby improving the rejection rate of multivalent ions. Commonly used negatively charged nanofiltration membrane materials include polyamide (introduced with carboxylic acid groups through interfacial polymerization) and sulfonated polysulfone (with -SO3 groups). - Materials such as polyethersulfone (PES) and surface-modified polyethersulfone can be used to adapt to different separation scenarios by controlling pore size distribution and surface charge density.
[0003] Despite the significant advantages of negatively charged nanofiltration membranes in water treatment, heavy metal removal, and dye desalination, key challenges remain to be addressed. The primary issue is the "trade-off" effect, where high rejection rates and high flux are difficult to achieve simultaneously. The permeability of existing negatively charged membranes is often limited by the charge density and thickness of the dense separation layer. Secondly, membrane fouling is more complex in negatively charged systems: while the negative charge on the membrane surface can repel negatively charged pollutants, it readily undergoes electrostatic adsorption with positively charged substances (such as proteins and cationic surfactants), leading to irreversible fouling. Furthermore, the decay of the membrane surface charge during long-term operation significantly reduces separation performance. To address these issues, current research focuses on the following technological improvements: (1) developing zwitterionic modified or gradient charge membrane layers to optimize antifouling properties; (2) constructing asymmetric charge structures to overcome trade-off limitations; and (3) introducing nanomaterials (such as COFs and MXene) to enhance the charge stability and permeation selectivity of the membrane structure. For example: CN116272446A discloses a method for preparing a negatively charged nanofiltration membrane based on piperazine-2-carboxylic acid. This method utilizes piperazine-2-carboxylic acid dissolved in water, with the pH adjusted using sodium hydroxide to obtain an aqueous phase. Trimethylbenzene chloride is dissolved in n-heptane to obtain an organic phase, followed by interfacial polymerization to finally obtain the negatively charged nanofiltration membrane. The high negative charge of this invention results in a sulfuric acid rejection rate greater than 98%, but its antifouling performance is insufficient and cannot meet industrial requirements.
[0004] For example, CN120204960A discloses a method for in-situ preparation of DABSA sulfonated modified composite nanofiltration membranes via interfacial polymerization. The method mainly involves dissolving DABSA in an alkaline aqueous phase (containing a phase transfer catalyst) while simultaneously preparing an organic monomer solution. The aqueous and organic phases are then sequentially impregnated onto the surface of a commercial polymer membrane via interfacial polymerization to form a primary layer. Finally, the DABSA sulfonated composite nanofiltration membrane is obtained through thermal crosslinking. This membrane can be applied to salt lake treatment, but its membrane flux is insufficient. Summary of the Invention
[0005] The main objective of this invention is to provide a negatively charged nanofiltration membrane, its preparation method, and its application, aiming to solve at least one technical problem existing in the prior art.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a negatively charged nanofiltration membrane, comprising the following steps: (1) Mix the first amine aqueous monomer solution and the second amine aqueous monomer solution, and then carry out an interfacial polymerization reaction with the acyl chloride oil monomer solution on the surface of the support layer to obtain the nanofiltration membrane to be modified. (2) The third amine aqueous monomer solution is subjected to a secondary interfacial polymerization reaction on the surface of the nanofiltration membrane to be modified obtained in step (1), followed by curing heat treatment to obtain a cured membrane; (3) The cured membrane obtained in step (2) is sequentially immersed in an oxidant solution and a polymer monomer solution to obtain the negatively charged nanofiltration membrane.
[0007] This invention utilizes interfacial polymerization to generate a polyamide separation layer on the surface of a support layer by mixing a first-amine aqueous monomer and a second-amine aqueous monomer with an acyl chloride oil monomer. Subsequently, a second interfacial polymerization is performed by introducing a third-amine aqueous monomer and residual acyl chloride groups on the membrane surface, successfully grafting a large number of sulfonic acid groups and thus enhancing the electronegativity of the membrane surface. Finally, the membrane is immersed in an oxidant, generating polymer reaction sites on the membrane surface. Then, polymer monomers are introduced for in-situ induced polymerization, ultimately forming a rigid, compact modified layer on the membrane surface. The resulting negatively charged nanofiltration membrane achieves effective retention of anions through the dual effects of pore size sieving and Donald's repulsion.
[0008] In step (3) of this invention, an in-situ induced polymerization method is used to construct a dense polymer layer on the surface of the nanofiltration membrane. Compared with traditional modification methods, this method forms active sites by chelating the oxidant with the residual amine group, and precisely controls the directional polymerization of polymer monomers. While ensuring uniform coverage of the charged layer, it effectively avoids the problem of membrane pore blockage and significantly improves membrane performance.
[0009] Preferably, in step (3), the oxidant includes any one or a combination of at least two of ammonium persulfate, ferric chloride, gold tetrachloride, potassium persulfate, and sodium persulfate.
[0010] Preferably, in step (3), the concentration of the oxidant solution is 0.1 to 1 mol / L, for example, it can be 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L, 0.9 mol / L or 1 mol / L, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0011] Preferably, in step (3), the time for the cured film to be immersed in the oxidant solution is 0.5 to 12 hours, for example, 1 hour, 3 hours, 5 hours, 7 hours, 9 hours, 11 hours or 12 hours, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0012] The specific operation of immersing the cured film in the oxidant solution of the present invention includes pouring the oxidant solution onto the surface of the cured film and letting it stand for 0.5 to 12 hours to allow the oxidant to fully react with the amine groups on the film surface, and then rinsing the film surface with deionized water to remove unreacted oxidant.
[0013] Preferably, in step (3), the concentration of the polymer monomer solution is 0.5 to 10 wt%, for example, it can be 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, or 5 wt%, more preferably 0.5 to 2.5 wt%, and even more preferably 1 to 2 wt%, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0014] The concentration of the polymer monomer solution described in this invention affects the thickness of the resulting modified layer, which in turn affects the performance of the nanofiltration membrane.
[0015] Preferably, in step (3), the polymer monomer includes nitrogen-containing monomer molecules and / or nitrogen-containing oligomer molecules. More preferably, the polymer monomer includes any one or a combination of at least two of pyrrole, sulfonated polyether ether ketone, sulfonated polybenzimidazole, polyacrylic acid, polymaleic anhydride, polycarboxylic betaine, and polyvinyl alcohol-sulfonated.
[0016] The polymer monomers described in this invention contain specific types of substances that can be adapted to achieve in-situ induced polymerization.
[0017] Preferably, in step (3), the time for the cured film to be immersed in the polymer monomer solution is 0.5 to 6 hours, for example, it can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0018] The present invention involves immersing the cured film in a polymer monomer solution by pouring the polymer monomer solution onto the surface of the cured film after oxidant treatment, and placing it in a constant temperature shaker. The temperature is adjusted to 20-40°C, for example, 20°C, 30°C, or 40°C, and the film is shaken at a constant temperature for 0.5-6 hours, for example, 0.5 hours, 1.5 hours, 2.5 hours, 3.5 hours, 4.5 hours, or 6 hours, so that the polymer can be effectively polymerized on the film surface.
[0019] Preferably, in step (2), the third amine aqueous monomer is an amine monomer that can undergo polycondensation reaction.
[0020] Preferably, the third amine aqueous phase monomer is benzidine, p-phenylenediamine, or piperazine. More preferably, the third amine aqueous phase monomer includes any one or at least two pure sulfonic acid monomers selected from 2-aminoethanesulfonic acid, benzidine dichloride, p-aminobenzenesulfonic acid, 4,4-diaminostilbene-2,2-disulfonic acid, N-(2-sulfonic acid ethyl)ethylenediamine, sulfonated triethylenetetramine, and p-phenylenediamine.
[0021] Preferably, in step (2), the concentration of the third amine aqueous monomer solution is 0.5 to 10 wt%, for example, it can be 0.5 wt%, 1.5 wt%, 2.5 wt%, 3.5 wt%, 4.5 wt%, 5.5 wt%, 6.5 wt%, 7.5 wt%, 8.5 wt%, 9.5 wt%, or 10 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable, and more preferably it is 0.5 to 2 wt%.
[0022] Preferably, in step (2), the time for the secondary interfacial polymerization reaction is 0.5 to 5 min, for example, it can be 0.5 min, 1.5 min, 2.5 min, 3.5 min, 4.5 min or 5 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0023] The time of the secondary interfacial polymerization reaction described in this invention not only affects the degree of removal of residual acyl chloride groups, but also affects the number of reaction sites for in-situ polymerization in step (3), thereby affecting the in-situ polymerization reaction in step (3) and the thickness of the modified layer.
[0024] Preferably, in step (2), the curing heat treatment temperature is 60 to 100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C, and the time is 10 to 20 minutes, for example, 10 minutes, 15 minutes or 20 minutes, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0025] Preferably, in step (1), the first aqueous amine monomer is an aliphatic amine or an aromatic amine. More preferably, the first aqueous amine monomer includes any one or a combination of at least two of piperazine, polyethyleneimine, m-phenylenediamine, p-phenylenediamine, triethanolamine, 4-methyl-m-phenylenediamine, and diaminotoluene.
[0026] Preferably, in step (1), the second amine aqueous phase monomer is a sulfonic acid amine. More preferably, the second amine aqueous phase monomer includes any one or a combination of at least two of the following: biphenyl diamine dichloride, 2,5-diaminobenzenesulfonic acid, 2-aminoethanesulfonic acid, p-aminobenzenesulfonic acid, 4,4-diaminostilbene-2,2-disulfonic acid, N-(2-sulfonic acid ethyl)ethylenediamine, and sulfonated triethylenetetramine.
[0027] Preferably, in step (1), the concentrations of the first aqueous amine monomer solution and the second aqueous amine monomer solution are 0.5 to 10 wt%, for example, 0.5 wt%, 2 wt%, 4 wt%, 6 wt%, 8 wt% or 10 wt%, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0028] Preferably, in step (1), the acyl chloride oil phase monomer includes any one or a combination of at least two of isophthaloyl chloride, isophthaloyl chloride 5-isocyanate, 5-chloroformoxy isophthaloyl chloride, 1,3,5-tricarboxyl chloride cyclohexane, biphenyltetracarboxyl chloride, biphenylpentacarboxyl chloride, and pyromellitic tricarboxyl chloride.
[0029] Preferably, in step (1), the concentration of the acyl chloride oil phase monomer solution is 0.5 to 5 wt%, for example, it can be 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt% or 5 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable. More preferably, the solvent of the acyl chloride oil phase monomer solution includes n-hexane or cyclohexane.
[0030] Preferably, in step (1), the time for the first interfacial polymerization reaction is 20 to 120 s, for example, it can be 20 s, 40 s, 60 s, 80 s, 100 s or 120 s, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0031] Preferably, step (1) specifically involves immersing the support layer in a mixed solution of a first amine aqueous monomer solution and a second amine aqueous monomer solution, then pouring out the mixed solution, removing the residual mixed solution using a rubber roller, allowing it to stand, and then pouring in an acyl chloride oil monomer solution for a single interfacial polymerization reaction. More preferably, the immersion time is 1 to 10 minutes, for example, 1 minute, 3 minutes, 5 minutes, 7 minutes, 9 minutes, or 10 minutes, but not limited to the listed values; other unlisted values within the range are also applicable. More preferably, the standing time is 1 to 5 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, or 5 minutes, but not limited to the listed values; other unlisted values within the range are also applicable.
[0032] Preferably, the support layer of the present invention comprises a polymer porous layer and / or a nonwoven fabric layer. More preferably, the polymer porous layer comprises any one or a combination of at least two of the following: a polyethersulfone porous layer, a polysulfone porous layer, a polyvinylidene fluoride porous layer, a polytetrafluoroethylene porous layer, and a polyethylene porous layer.
[0033] Preferably, the thickness of the support layer is 100–400 μm, for example, 100 μm, 200 μm, 300 μm or 400 μm, and the molecular weight cutoff is 5000–100000 Da, for example, 5000 Da, 10000 Da, 30000 Da, 50000 Da, 70000 Da, 90000 Da or 100000 Da, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0034] Preferably, in step (1), the support layer is pretreated first, and then an interfacial polymerization reaction is performed. More preferably, the pretreatment method includes immersing the support layer in deionized water for 12 to 24 hours, for example, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0035] In a second aspect, the present invention provides a negatively charged nanofiltration membrane, which is prepared by the preparation method described in the first aspect.
[0036] Thirdly, the present invention provides an application of the negatively charged nanofiltration membrane as described in the second aspect in the treatment of desalinated seawater or industrial wastewater.
[0037] This invention utilizes interfacial polymerization technology to prepare a composite nanofiltration membrane with a high negative charge density. This negatively charged nanofiltration membrane is effective against SO42-. 2-This membrane material exhibits excellent retention performance for anions and high-valence heavy metal ions, while also possessing high water flux, antifouling properties, and long-term stability. It can significantly improve the removal efficiency of anionic pollutants and extend membrane lifespan, meeting the application needs of industrial wastewater treatment, heavy metal recovery, and other fields.
[0038] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, a negatively charged polyamide separation layer is formed on the support layer through two interfacial polymerizations, and a large number of sulfonic acid groups are grafted onto it. Then, a rigid modified layer is introduced through in-situ induced polymerization. The combination of these two layers greatly enhances the negative charge, hydrophilicity and stability of the membrane surface.
[0039] (2) The negatively charged composite nanofiltration membrane provided by the present invention achieves effective retention of divalent anions under the dual effects of Dornan repulsion and pore size sieving. Furthermore, the presence of the modified layer improves the hydrophilicity of the membrane surface, resulting in a significant increase in membrane flux. Attached Figure Description
[0040] Figure 1 This is a SEM image of the negatively charged composite nanofiltration membrane described in Embodiment 1 of the present invention.
[0041] Figure 2 This is a SEM image of the negatively charged composite nanofiltration membrane described in Embodiment 4 of the present invention.
[0042] Figure 3 This is a SEM image of the negatively charged composite nanofiltration membrane described in Embodiment 5 of the present invention.
[0043] Figure 4 This is a SEM image of the negatively charged composite nanofiltration membrane described in Embodiment 6 of the present invention.
[0044] Figure 5 This is a SEM image of the negatively charged composite nanofiltration membrane described in Comparative Example 1 of the present invention.
[0045] Figure 6 This is a SEM image of the negatively charged composite nanofiltration membrane described in Comparative Example 2 of the present invention. Detailed Implementation
[0046] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.
[0047] Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial sources or by existing known methods; unless otherwise specified, the methods used in the embodiments of the present invention are methods mastered by those skilled in the art.
[0048] Example 1 Preparation of negatively charged nanofiltration membranes The preparation method includes the following steps: (1) Using polyethersulfone ultrafiltration membrane (Changsha Huamo Water Treatment Technology Co., Ltd., UE020) as the support layer, it was first soaked in deionized water for 24h. Then, a mixture of 1.6wt% piperazine solution and 0.4wt% benzidine dichloride solution (volume ratio 1:1) was prepared and poured onto the surface of the ultrafiltration membrane. After immersion for 2min, it was poured out. The residual solution on the membrane surface was removed with a rubber roller and allowed to stand for 4min. Then, a prepared 0.15wt% trimesoyl chloride solution was poured in and reacted for 60s before being quickly poured out to obtain the nanofiltration membrane to be modified. (2) Pour a 1 wt% solution of benzidine dichloride into the surface of the nanofiltration membrane to be modified obtained in step (1), react for 2 min and then take it out. Then put the membrane into an 80℃ oven and let it stand for 10 min before taking it out to obtain a cured membrane. (3) Pour the prepared 1 mol / L ferric chloride solution onto the surface of the cured membrane obtained in step (2), react for 12 h, rinse the membrane surface with deionized water to remove excess oxidant, and then pour in the prepared 1.5 wt% pyrrole solution and shake at 30 °C for 2 h to obtain a negatively charged nanofiltration membrane.
[0049] The SEM image of the negatively charged nanofiltration membrane prepared in this embodiment is shown below. Figure 1 As shown.
[0050] Example 2 Preparation of negatively charged nanofiltration membranes The preparation method includes the following steps: (1) Using polyethersulfone ultrafiltration membrane (Changsha Huamo Water Treatment Technology Co., Ltd., UE020) as the support layer, it was first soaked in deionized water for 18h. Then, a 1.6wt% p-phenylenediamine solution and a 0.4wt% biphenylenediamine dichloride solution were mixed (volume ratio 1:1) and poured onto the surface of the ultrafiltration membrane. After immersion for 1min, the solution was poured out. The residual solution on the membrane surface was removed with a rubber roller and allowed to stand for 5min. The prepared 5wt% trimesoyl chloride solution was poured in and reacted for 20s before being poured out to obtain the nanofiltration membrane to be modified. (2) Pour a 1 wt% p-phenylenediamine solution onto the surface of the nanofiltration membrane to be modified obtained in step (1), react for 0.5 min and then remove it. Then place the membrane in a 100℃ oven and let it stand for 10 min before removing it to obtain a cured membrane. (3) Pour the prepared 0.5 mol / L ferric chloride solution onto the surface of the cured membrane obtained in step (2), react for 6 h, rinse the membrane surface with deionized water to remove excess oxidant, and then pour in the prepared 0.5 wt% pyrrole solution and shake at 20 °C for 5 h to obtain a negatively charged nanofiltration membrane.
[0051] Example 3 Preparation of negatively charged nanofiltration membranes The preparation method includes the following steps: (1) Using polyethersulfone ultrafiltration membrane (Changsha Huamo Water Treatment Technology Co., Ltd., UE020) as the support layer, it was first soaked in deionized water for 12h. Then, 1wt% piperazine solution and 1wt% benzidine dichloride solution were mixed (volume ratio 1:1) and poured onto the surface of the ultrafiltration membrane. After immersion for 10min, it was poured out. The residual solution on the membrane surface was removed with a rubber roller and allowed to stand for 1min. Then, 0.15wt% pyromellitic acid chloride solution was poured in and reacted for 120s before being poured out to obtain the nanofiltration membrane to be modified. (2) Pour a 1 wt% solution of benzidine dichloride into the surface of the nanofiltration membrane to be modified obtained in step (1), react for 5 min and then remove it. Then place the membrane in a 60℃ oven and let it stand for 20 min before removing it to obtain a cured membrane. (3) Pour the prepared 0.1 mol / L ferric chloride solution onto the surface of the cured membrane obtained in step (2), react for 12 h, rinse the membrane surface with deionized water to remove excess oxidant, and then pour in the prepared 0.5 wt% pyrrole solution and shake at 40 °C for 0.5 h to obtain a negatively charged nanofiltration membrane.
[0052] Example 4 Preparation of negatively charged nanofiltration membranes The preparation method of this embodiment is basically the same as that of embodiment 1, except that the concentration of the pyrrole solution in step (3) is adjusted to 0.5 wt%.
[0053] The SEM image of the negatively charged nanofiltration membrane prepared in this embodiment is shown below. Figure 2 As shown.
[0054] Example 5 Preparation of negatively charged nanofiltration membranes The preparation method of this embodiment is basically the same as that of embodiment 1, except that the concentration of the pyrrole solution in step (3) is adjusted to 1 wt%.
[0055] The SEM image of the negatively charged nanofiltration membrane prepared in this embodiment is shown below. Figure 3 As shown.
[0056] Example 6 Preparation of negatively charged nanofiltration membranes The preparation method of this embodiment is basically the same as that of embodiment 1, except that the concentration of the pyrrole solution in step (3) is adjusted to 2wt%.
[0057] The SEM image of the negatively charged nanofiltration membrane prepared in this embodiment is shown below. Figure 4 As shown.
[0058] Example 7 Preparation of negatively charged nanofiltration membranes The preparation method of this embodiment is basically the same as that of embodiment 1, except that the concentration of the benzidine dichloride solution in step (2) is adjusted to 0.5 wt%.
[0059] Example 8 Preparation of negatively charged nanofiltration membranes The preparation method of this embodiment is basically the same as that of embodiment 1, except that the concentration of the benzidine dichloride solution in step (2) is adjusted to 1.5 wt%.
[0060] Comparative Example 1 Comparison of nanofiltration membrane preparation The preparation method includes the following steps: (1) Using polyethersulfone ultrafiltration membrane (Changsha Huamo Water Treatment Technology Co., Ltd., UE020) as the support layer, it was first soaked in deionized water for 24h. Then, a mixture of 1.6wt% piperazine solution and 0.4wt% benzidine dichloride solution (volume ratio 1:1) was prepared and poured onto the surface of the ultrafiltration membrane. After immersion for 2min, it was poured out. The residual solution on the membrane surface was removed with a rubber roller and allowed to stand for 4min. Then, a prepared 0.15wt% trimesoyl chloride solution was poured in and reacted for 60s before being quickly poured out to obtain the nanofiltration membrane to be modified. (2) The nanofiltration membrane to be modified obtained in step (1) was placed in an 80℃ oven and left to stand for 10 minutes before being taken out to obtain a control nanofiltration membrane. Its SEM image is shown below. Figure 5 As shown.
[0061] Comparative Example 2 Comparison of nanofiltration membrane preparation The preparation method includes the following steps: (1) Using polyethersulfone ultrafiltration membrane (Changsha Huamo Water Treatment Technology Co., Ltd., UE020) as the support layer, it was first soaked in deionized water for 24h. Then, a mixture of 1.6wt% piperazine solution and 0.4wt% benzidine dichloride solution (volume ratio 1:1) was prepared and poured onto the surface of the ultrafiltration membrane. After immersion for 2min, it was poured out. The residual solution on the membrane surface was removed with a rubber roller and allowed to stand for 4min. Then, a prepared 0.15wt% trimesoyl chloride solution was poured in and reacted for 60s before being quickly poured out to obtain the nanofiltration membrane to be modified. (2) A 1 wt% solution of benzidine dichloride was poured onto the surface of the nanofiltration membrane to be modified obtained in step (1). After reacting for 2 minutes, the membrane was removed and placed in an 80°C oven for 10 minutes before being removed to obtain a control nanofiltration membrane. Its SEM image is shown below. Figure 6 As shown.
[0062] Comparative Example 3 Comparison of nanofiltration membrane preparation The preparation method of this comparative example is basically the same as that of Example 1. The only difference is that the ferric chloride solution treatment in step (3) is omitted in this comparative example. The cured film obtained in step (2) is directly poured into 1.5wt% pyrrole solution and shaken at 30°C for 2 hours.
[0063] Experimental Example: Performance Testing of Nanofiltration Membranes The nanofiltration membranes prepared in the above embodiments and comparative examples were subjected to retention performance tests and membrane flux tests.
[0064] Selective Retention Performance Test: The single salt retention performance of the nanofiltration membrane was tested using a nanofiltration cross-flow device. Membrane sheets were cut to a specific size and placed in the membrane tank, with an effective area of 28.26 cm². 2 After pre-pressing at 0.6 MPa for 60 min to stabilize the membrane performance, it was tested. The feed solution was 2000 ppm Na2SO4 solution. This was used to determine the rejection rate of the nanofiltration membrane for the two single salts. The specific calculation formula is as follows:
[0065] Where: R—retention rate (%); C p — Permeate solute concentration (mg / L); C f —Solute concentration in the feed solution (mg / L).
[0066] Membrane flux testing: Membrane flux was also measured using a nanofiltration cross-flow device. Membrane flux refers to the volume of permeate passing through a unit area per unit time during membrane separation under certain conditions. The specific calculation formula is as follows:
[0067] Where: J—permeability flux (L·m -2 ·h -1 • bar); V—permeate volume (L); A—effective membrane area (m²) 2 P—Transmembrane pressure (bar); T—Permeation time (h).
[0068] Nanofiltration membrane characterization tests: (1) Scanning electron microscope: The surface morphology of the composite nanofiltration membrane was determined using a Hitachi S4800 thermal field emission scanning electron microscope. Before the test, the nanofiltration membrane needed to be thoroughly dried, and then its surface was sputtered with gold for testing.
[0069] (2) Contact angle: The contact angle of the composite nanofiltration membrane was measured using a DSA30 contact angle meter and the hydrophilicity of the membrane surface was analyzed. Before the test, the membrane was thoroughly dried and then cut into appropriate sizes and fixed on a glass slide with double-sided tape. The glass slide was placed on the stage and then a fixed distance was adjusted to drop a fixed size of pure water droplet onto the membrane surface. After the droplet stayed on the membrane surface for 10 seconds, the size of the droplet was photographed and the contact angle of the droplet was measured. Each membrane sample was measured three times and the average value was taken.
[0070] (3) Zeta potential: The Zeta potential of the composite nanofiltration membrane was measured and the surface charge of the membrane was analyzed using a SurPASS3 Zeta potential meter. The membrane sample was cut into appropriate sizes, and the pH range of 3-10 was tested using 1 mmol / L potassium chloride solution as electrolyte to obtain the Zeta potential values at different pH values.
[0071] The test results are shown in Table 1: Table 1
[0072] As can be seen from Table 1: (1) As can be seen from Example 1 and Comparative Examples 1-3, when another aqueous monomer is incorporated into the membrane surface in this invention, the diamine group reacts with the acyl chloride group, resulting in the complete reaction of the acyl chloride group on the membrane surface and the grafting of a large number of sulfonic acid groups. Then, a rigid modified layer is introduced through in-situ induced polymerization, which greatly enhances the negative charge, hydrophilicity, and stability of the membrane surface. Furthermore, through comparison... Figure 1 and Figure 5 and Figure 6 It was found that the cross-linked network structure and nodular structure on the membrane surface were transformed into a more uniform layered structure; as shown in Comparative Examples 1-3, the membrane performance was successfully improved through continuous polymerization and interlayer regulation.
[0073] (2) As can be seen from Example 1 and Comparative Example 3, the present invention requires the use of an oxidant to treat the polymer monomers first, so that the oxidant chelates with the amine group to form a reaction site, and then the polymer monomers are induced to polymerize in situ to obtain the modified layer. Comparative Example 3 did not use polymer monomers for polymerization or did not use an oxidant, so it was impossible to obtain an effective modified layer.
[0074] (3) As can be seen from Examples 1 and 2-3, the membrane performance exhibited by the present invention varies when using different reactive monomers and different reaction concentrations. By comparing Examples 1 and 4-6, it can be seen that the pyrrole concentration has a significant impact on the membrane performance. The retention rate is significantly improved by introducing the pyrrole modified layer, while the membrane flux does not change significantly, thus successfully overcoming the trade-off effect and enhancing the membrane performance.
[0075] (3) As can be seen from Examples 1 and 7-8, secondary polymerization by adding different concentrations of benzyldiamine dichloride solution can significantly improve the hydrophilicity and negative charge of the membrane surface, and enhance the retention of anions while increasing the membrane flux.
[0076] In summary, the negatively charged nanofiltration membrane prepared by interfacial polymerization in this invention not only effectively removes SO42- but also... 2- Plasma has a high rejection rate, as well as high membrane flux and stability, which enhances the working efficiency and service life of nanofiltration membranes, enabling nanofiltration membranes to be used in industrial applications.
[0077] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a negatively charged nanofiltration membrane, characterized in that, Includes the following steps: (1) Mix the first amine aqueous monomer solution and the second amine aqueous monomer solution, and then carry out an interfacial polymerization reaction with the acyl chloride oil monomer solution on the surface of the support layer to obtain the nanofiltration membrane to be modified. (2) The third amine aqueous monomer solution is subjected to a secondary interfacial polymerization reaction on the surface of the nanofiltration membrane to be modified obtained in step (1), followed by curing heat treatment to obtain a cured membrane; (3) The cured membrane obtained in step (2) is sequentially immersed in an oxidant solution and a polymer monomer solution to obtain the negatively charged nanofiltration membrane.
2. The method for preparing a negatively charged nanofiltration membrane as described in claim 1, characterized in that, In step (2), the third amine aqueous monomer is an amine monomer that can undergo polycondensation reaction; the concentration of the third amine aqueous monomer solution is 0.5-10 wt%; the time of the secondary interfacial polymerization reaction is 30-300 s; the temperature of the curing heat treatment is 50-100℃ and the time is 5-20 min.
3. The method for preparing a negatively charged nanofiltration membrane as described in claim 1 or 2, characterized in that, In step (3), the oxidant includes any one or a combination of at least two of ammonium persulfate, ferric chloride, gold tetrachloride, potassium persulfate, and sodium persulfate; the concentration of the oxidant solution is 0.1 to 1 mol / L, and the time for the cured film to be immersed in the oxidant solution is 0.5 to 24 h.
4. The method for preparing a negatively charged nanofiltration membrane as described in claim 1 or 2, characterized in that, In step (3), the polymer monomer includes any one or a combination of at least two of pyrrole, sulfonated polyether ether ketone, sulfonated polybenzimidazole, polyacrylic acid, polymaleic anhydride, polycarboxylic betaine, and polyvinyl alcohol-sulfonated; the concentration of the polymer monomer solution is 0.5 to 10 wt%, and the time for the cured film to be immersed in the polymer monomer solution is 0.5 to 6 h.
5. The method for preparing a negatively charged nanofiltration membrane as described in claim 1 or 2, characterized in that, In step (1), the first amine aqueous phase monomer is an aliphatic amine or an aromatic amine; the concentration of the first amine aqueous phase monomer solution is 0.5 to 10 wt%.
6. The method for preparing a negatively charged nanofiltration membrane as described in claim 1 or 2, characterized in that, In step (1), the second amine aqueous phase monomer is a sulfonic acid amine; the concentration of the second amine aqueous phase monomer solution is 0.5 to 10 wt%.
7. The method for preparing a negatively charged nanofiltration membrane as described in claim 1 or 2, characterized in that, In step (1), the acyl chloride oil phase monomer includes any one or a combination of at least two of isophthaloyl chloride, isophthaloyl chloride 5-isocyanate, 5-chloroformoxybenzoyl chloride, 1,3,5-tricarboxyyl chloride cyclohexane, biphenyltetracarboxyyl chloride, biphenylpentacarboxyyl chloride, and pyromellitic tricarboxyyl chloride; the concentration of the acyl chloride oil phase monomer solution is 0.5-5 wt%; and the time for one interfacial polymerization reaction is 20-120 s.
8. The method for preparing a negatively charged nanofiltration membrane as described in claim 1 or 2, characterized in that, The thickness of the support layer is 100–400 μm, and the molecular weight cutoff is 5000–100000 Da.
9. A negatively charged nanofiltration membrane, characterized in that, Prepared according to the preparation method of any one of claims 1 to 8.
10. The application of the negatively charged nanofiltration membrane as described in claim 9 in industrial wastewater treatment.
Citation Information
Patent Citations
Preparation method of negatively charged nanofiltration membrane based on piperazine-2-carboxylic acid
CN116272446A
Method for in-situ preparation of DABSA sulfonated modified composite nanofiltration membrane through interfacial polymerization
CN120204960A